Disparities in Access to Virtual Care for Urinary Tract Infections During the COVID-19 Era - Molly E. DeWitt-Foy; Jacob A. Albersheim; Shawn T. Grove; Lina Hamid; Sally Berryman; Sean P. Elliott (Société Internationale d’Urologie Journal, 2023)
ObjectiveTo characterize the difference in uptake of virtual care for urinary tract infections (UTIs) by demographic variables in the COVID-19 era. MethodsWe conducted a retrospective review of outpatient encounters for UTIs across a large health care system. The cohort was defined as patients with an encounter diagnosis of UTI via in-person or virtual care (telephone or technology-supported care), between March 1, 2020, and February 28, 2021. Analysis was limited to the first UTI encounter of the year for each patient. We compared the use of in-person and virtual visits by demographic variables using chi-square tests and multivariate logistic regression. ResultsA total of 6744 patients, with a mean age of 61 years, were seen for UTI during the study period. The majority of patients were White (85.5%) and female (83.7%), and were seen in person (55.9%). Of those seen virtually, 52.0% participated in telephone-only visits, and 47.9% were seen via technology-supported care, using video or chat-based platforms. On multivariate logistic regression, age under 30, lowest-quartile income, male sex, and a primary language other than English increased the odds that patients had been seen in person. Among those seen virtually, age over 50 significantly increased the odds of a telephone visit, as did being Black or Native American, having a lower-quartile income, and speaking a non-English primary language. ConclusionsAlthough the expansion in virtual care has given some patients easier access to necessary care, the “digital divide” has worsened existing disparities for certain vulnerable populations. We demonstrate a difference in uptake of virtual health care by age, race, primary language, and income.